Empowerment of Mustaḥiq Zakat Model Towards Business Independency - Hamzah Hamzah (International Journal of Nusantara Islam, 2017)
Zakat has not been utilized intensively for the empowerment of mustaḥiq (zakat beneficiaries) in the form of productive economic business. The objective of the research was to analyze the level of mustaḥiqs’ business independency; to analyze dominant factors that influenced mustaḥiqs’ business independency, and to formulate an appropriate strategy to develop the mustaḥiqs’ business independency. The research has been carried out on 254 mustaḥiqs in Bogor Regency (66 mustaḥiqs engaged in vegetable production at Cibungbulang District, 85 mustaḥiqs in skewer business at Tenjolaya District, and 103 mustaḥiqs in shoe business at Taman Sari District). A census sampling, data collection through a questionnaire, an in-depth interview and observation were carried out in 2013. Data were analyzed descriptively and statistically, using structural equation model (SEM). The results of the research showed that: (1) the strategy of mustaḥiq empowerment could be carried out through strengthening the intrinsic motivation, training technical aspects, assisting business capital and assistance. Empowerment can be conducted synergically by the government (arrangement, service, and counseling), private sectors/State Owned Business (BUMN), higher education and community.